Observasi dalam Mencipta Karya Seni - Nick Soedarso; Barry Carvey (Bina Nusantara University, 2012)
In the beginning of creating a work of art, an observation of the problem is needed. A new representation of an existing form, would not become a newness if not display novelty and actuality, as it will only produce something similar, and repetition, so it will not be a result of creativity.